Indonesia Guidelight Project dan Tafsir Audiovisual: Tinjauan atas Metodologi Tafsir dan Kontribusinya di Masa Pandemi - Mamluatun Nafisah; Nur Azizah Trijayanti (Fakultas Ushuluddin dan Dakwah Institut Ilmu Al-Qur'an (IIQ) Jakarta, Indonesia, 2021)
This paper departs from the many platforms on social media that offer virtual Al-Qur’an learning facilities, especially during the pandemic. One of the platforms on social media that facilitates virtual Al-Qur’an learning is the Indonesia Guidelight Project. To find out how the methodology for audiovisual interpretation of the Indonesia Guidelight Project is and how the contribution and reception of participants to the study is, the author uses the phenomenological approach initiated by Edmund Husserl and the interpretation approach. The results of this study conclude that the Guidelight audiovisual interpretation provides a positive contribution to the wider community so as to increase their understanding of the content of the Quran and become a better person. In addition, if you look at the methodological aspect, the audiovisual interpretation of Guidelight is substantially informative by presenting resource persons who have appropriate competence as exegetes. It's just that for the good of the future the form of interpretation is enriched with contextual approaches.